PERAN WORD OF MOUTH MEMEDIASI PENGARUH KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN (STUDI PADA KONSUMEN INDIHOME DI KOTA DENPASAR) - Pharamadita, I Putu Agus Wenta; Santika, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.04.TAHUN.2024DO - 10.24843/EEB.2024.v13.i04.p11, 2024)
In the era of globalization, the need for the internet is very high. The number of companies makes competition increasingly fierce so it is important for companies to pay attention to things that can influence the purchasing decisions of their consumers. The purpose of this study was to explain the role of word of mouth in mediating the influence of product quality on purchasing decisions for indihome consumers in Denpasar City. This research was conducted on indihome consumers in Denpasar City. The sampling technique used in this research is nonprobability sampling technique with the number of samples used is 100 respondents with purposive sampling method. Data collection was carried out through distributing questionnaires. The collected data were analyzed using Path Analysis techniques, Sobel Test and VAF Test. The results of this study indicate that product quality has a positive and significant effect on purchasing decisions; product quality has a positive and significant effect on word of mouth; word of mouth has a positive and significant effect on purchasing decisions; word of mouth is a partially mediating variable for the effect of product quality on purchasing decisions for Indihome consumers in Denpasar City.